1998
DOI: 10.1111/j.1469-7793.1998.827bg.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of transient outward current by extracellular protons and Cd2+ in rat and human ventricular myocytes

Abstract: 1. The effects of extracellular acidosis and Cd¥ on the transient outward current (Ito) have been investigated in rat and human ventricular myocytes, using the whole-cell patch-clamp technique. 2. In rat myocytes, exposure to acidic extracellular solution (pH 6·0) shifted both steady-state activation and inactivation curves to more positive potentials, by 20·5 ± 2·7 mV (mean ± s.e.m.; n = 4) and 19·8 ± 1·2 mV, respectively. Cd¥ also shifted the activation and inactivation curves in a positive direction in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 29 publications
(34 reference statements)
2
31
1
1
Order By: Relevance
“…The "high" threshold for activation of the transient currents and their sensitivity to Iso also make it unlikely that they were due to monovalent cation flow through T-type Ca 2ϩ channels. Finally, although nifedipine has been shown to block a variety of native or expressed K ϩ channels with low affinity (10,32), extracellular divalent cations are not known to block I to [except from a shift of the voltage-dependent activation and inactivation (12,27)], and I to is not increased by ␤-adrenergic receptor stimulation. We are therefore left with the hypothesis that they are due to L-type Ca 2ϩ channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "high" threshold for activation of the transient currents and their sensitivity to Iso also make it unlikely that they were due to monovalent cation flow through T-type Ca 2ϩ channels. Finally, although nifedipine has been shown to block a variety of native or expressed K ϩ channels with low affinity (10,32), extracellular divalent cations are not known to block I to [except from a shift of the voltage-dependent activation and inactivation (12,27)], and I to is not increased by ␤-adrenergic receptor stimulation. We are therefore left with the hypothesis that they are due to L-type Ca 2ϩ channels.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane currents were measured as previously described (12,27) using the whole cell patch-clamp technique (11). Heatpolished borosilicate glass electrodes (horizontal puller, Zeitz Instrumente; Munich, Germany) with tip resistances of 1-1.5 M⍀ when filled with the internal solution were used.…”
Section: Methodsmentioning
confidence: 99%
“…We also studied the indirect action of these repolarization changes on I Ca,L and CaTs. In contrast to previous reports of pH effects on ventricular I to (24,50,58,59), our experiments were performed at physiological temperature with a myocyte preparation with a more humanlike AP than that of rat.…”
Section: Discussionmentioning
confidence: 75%
“…Previous work with rat ventricular myocytes, measured at room temperature, reported that both extracellular acidosis (50) and simultaneous reductions in pH o and pH i (24) (Fig. 3A), as also observed in rat ventricular myocytes (50).…”
Section: Effect Of Acidosis and Cadmium On Steady-state Voltage Depenmentioning
confidence: 80%
See 1 more Smart Citation